The Effect of the "One Day One Hour" Method in Reading the Qur'an on Improving Short-Term Memory in Students of the Faculty of Medicine, Muhammadiyah University of North Sumatra - Odilla Meissy Adyatma; Maulana Siregar (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Short-term memory is a temporary storage of information with limited capacity. The ODOH (One Day One Hour) method is a program of reading the Qur'an for one hour every day that can improve brain function, concentration, and memory. This study aims to analyze the effect of reading the Qur'an on short-term memory with a digit span test on students of the Faculty of Medicine, Muhammadiyah University of North Sumatra. Objective: to measure short-term memory using a digit span test after reading the Qur'an Method: This study used a quantitative research method with a quasi-experimental design with a Non-Equivalent Control Group approach. The research subjects were 20 people who were taken using a purposive sampling method. Results: The results of the hypothesis test with Paired Sample T-Test showed that the "One Day One Hour" method had no significant effect on improving short-term memory on the forward test, because there was no significant difference between the pretest (5.9) and posttest (6.4). However, in the backward test, there was a significant increase from the pretest (4.1) to the posttest (5.3). Conclusion: There was no significant increase in the short-term memory of the experimental group using the forward digit span test, but there was a significant increase in the backward test.